2014
DOI: 10.5935/1676-2444.20140029
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications and histological correlation of atypical glandular cells found in cervicovaginal smears

Abstract: Introduction: Atypical glandular cells (AGC) are carriers of insufficient nuclear abnormalities for the diagnosis of adenocarcinoma, but exceed the criteria for classification as reactive glandular cells. This is an uncommon diagnosis, which may be associated with neoplastic lesions. Objective: To evaluate the clinical significance of primary cytological diagnosis of AGC through correlation with results of subsequent cyto-histologic examination. Materials and methods: 10 years retrospective study based on cerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
2
0
0
Order By: Relevance
“…9 Evidences from previous studies evaluating histological results in women with a diagnosis of AGC have shown that it includes a range of benign changes as well as cervical precursor lesions of glandular and/or squamous origins to invasive cervical cancer and other gynaecological cancers. 10 In the present study ,the prevalence of diagnostic category of AGC was 0.05% which is comparable with study by Loos et al 11 ,quoting 0.06 % prevalence of AGC among cervical smears. In our study 53% of cases were benign diagnoses on subsequent biopsy and 47% had malignancy.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…9 Evidences from previous studies evaluating histological results in women with a diagnosis of AGC have shown that it includes a range of benign changes as well as cervical precursor lesions of glandular and/or squamous origins to invasive cervical cancer and other gynaecological cancers. 10 In the present study ,the prevalence of diagnostic category of AGC was 0.05% which is comparable with study by Loos et al 11 ,quoting 0.06 % prevalence of AGC among cervical smears. In our study 53% of cases were benign diagnoses on subsequent biopsy and 47% had malignancy.…”
Section: Discussionsupporting
confidence: 90%
“…13 Similarly Loos et al revealed 46.9% malignant lesions on histological follow up of AGC diagnosis. 11 In the present study histopathological correlation revealed 39 out of the 66 malignant cases(in situ and invasive) to be of glandular origin (59%) while the remaining 27 (40%) cases to be of squamous origin . The proportion of adenocarcinoma is higher as compared to previous studies which quote higher percentage of invasive squamous cell carcinoma diagnosed through a histopathological analysis in patients with AGC as mentioned in six articles, [15][16][17][18][19][20] of which five were published from 2003 to 2009.…”
Section: Discussionsupporting
confidence: 54%